2017
DOI: 10.1038/srep42975
|View full text |Cite
|
Sign up to set email alerts
|

Greener Route for Synthesis of aryl and alkyl-14H-dibenzo [a.j] xanthenes using Graphene Oxide-Copper Ferrite Nanocomposite as a Recyclable Heterogeneous Catalyst

Abstract: A facile, efficient and environmentally-friendly protocol for the synthesis of xanthenes by graphene oxide based nanocomposite (GO-CuFe2O4) has been developed by one-pot condensation route. The nanocomposite was designed by decorating copper ferrite nanoparticles on graphene oxide (GO) surface via a solution combustion route without the use of template. The as-synthesized GO-CuFe2O4 composite was comprehensively characterized by XRD, FTIR, Raman, SEM, EDX, HRTEM with EDS mapping, XPS, N2 adsorption-desorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 98 publications
0
40
1
Order By: Relevance
“…Previously reported synthesis of pharmaceutically 14-aryl-14-Hdibenzo [a,j]xanthenes compared with our catalysts showed that the efficiency of Fe-Mg MOF was so higher than that of several reported catalysts e.g. nano-ZnAl 2 O 4 , 52 acid activated clay in Kerman Province, 53 graphene oxide-copper ferrite nanocomposite, 54 palladium nanoparticles supported on amino-functionalized MOFs and zinc oxide nanoparticles. 55 The comparison study not only depended on the percentage yield of the desired product but also the condition required optimizing the reaction.…”
Section: Surface Aciditycontrasting
confidence: 58%
“…Previously reported synthesis of pharmaceutically 14-aryl-14-Hdibenzo [a,j]xanthenes compared with our catalysts showed that the efficiency of Fe-Mg MOF was so higher than that of several reported catalysts e.g. nano-ZnAl 2 O 4 , 52 acid activated clay in Kerman Province, 53 graphene oxide-copper ferrite nanocomposite, 54 palladium nanoparticles supported on amino-functionalized MOFs and zinc oxide nanoparticles. 55 The comparison study not only depended on the percentage yield of the desired product but also the condition required optimizing the reaction.…”
Section: Surface Aciditycontrasting
confidence: 58%
“…Recorded XPS patterns of pristine and decorated GO are illustrated in Fig. 1a [42,43]. X-ray diffraction patterns were recorded to confirm the formation of the support as well as the composite, and data are shown in Fig.…”
Section: Preliminary Confirmation and Structural Studiesmentioning
confidence: 99%
“…A mixture of arylaldehyde (1 mmol), 2-naphthol (2 mmol) and [TEASA][TFA] (0.044 g, 0.15 mmol) was initially stirred by a magnet at 100 °C, and after the reaction was solidified, it was stirred with a small rod at that temperature. After the reaction was completed {as monitored by TLC) n-hexane/ethyl acetate: 3/1)} , the mixture was cooled to room temperature, and the solid residue (crude product) was purified by recrystallization from hot ethanol (95%) [8,[32][33][34][35][36][37][38][39][40].…”
Section: General Procedures For the Production Of 14-aryl-14h-dibenzo[mentioning
confidence: 99%
“…Moreover, these compounds can be applied as pHsensitive fluorescent materials for visualization of biomolecules, as sensitizers in photodynamic therapy, and in laser technology [29][30][31]. The general method for synthesis of 14-aryl-14Hdibenzo [a,j]xanthenes, as a significant class of xanthenes, involves the reaction of arylaldehydes with 2-naphthol in the presence of a catalyst [8,[32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%